Investigation of Chemokine Receptor CCR2V64Il Gene Polymorphism and Migraine without Aura in the Iranian Population - Alireza Zandifar; Maryam Taheriun; Samira Soleimani; Faraidoon Haghdoost; Mohamadhasan Tajaddini; Shaghayegh Haghjooy Javanmard (The Scientific World Journal)
Background and Objectives. Migraine is a multifactorial common neurovascular disease with a polygenic inheritance. Inflammation plays an important part in migraine pathophysiology. C-C chemokine receptor 2 (CCR2) is an important chemokine for monocyte aggregation and transendothelial monocyte migration. The aim of our study was to investigate the association of migraine with CCR2V64Il polymorphism in the Iranian population. Methods. We assessed 103 patients with newly diagnosed migraine and 100 healthy subjects. Genomic DNA samples were extracted from peripheral blood and genotypes of CCR2V64Il gene polymorphism were determined. For measuring the severity of headache, every patient filled out the MIGSEV questionnaire. Results. There were no significant differences in the distribution of both 64Il allele and heterozygote (GA) genotype of CCR2 gene polymorphism (P=0.396; OR=0.92, 95% CI = 0.50–1.67 and P=0.388; OR=0.91, 95% CI = 0.47–1.73, resp.) between case and control groups. There was no significant difference of alleles frequency between three grades of MIGSEV (P=0.922). Conclusions. In conclusion our results revealed no association between CCR2V64Il polymorphism and susceptibility to migraine and also headache severity in the Iranian population.